Maqâshid al-Qurân Perspektif Badi’uzzaman Sa’id Nursi : (Telaah Penafsiran Surat Al-Fatihah dalam Kitab Rasâil al-Nûr) - Ummu Salamah (Universitas Darussalam Gontor, 2019)
The texts in the Holy Qur’an are global characteristic, to understand, it required many studies and new scientific approach in accordance with the development of human life. One of them was through the maqashid al-Qur’an . However ,there were some theologian who had different concept than other in appliying the maqashid al-Qur-an. One of them was Badi al-Zaman Sa’id al-Nursi through his creation Rasail al-Nur, when he was interpreted of surah al-Fatihah through this approach he could make different interpretation, and he had own uniqueness and characteristic. Therefore, the writer wants to analyze the concept of maqashid a;-Qur’an in the prespektive of Badi al-Zaman Said al-Nursi and the content of maqashid al-Qur’an in surah al-Fatihah in his creation Rasail al-Nur. Then, the writer used munasabat science approach for analysing the interpretation of Badi al-Zaman Sa’id Nursi about the content of maqashid al-Qur’an in surah al-Fatihah. Which that will produce of conclusion that maqashid al-Qur’an in surah al-Fatihah to be four objectives categorized as : al-Tauhîd, al-Nubuwah, al-hashr, wa al-‘adâlah”. In meaning that the Holy Qur’an revealed with four main objectives such tauhidy, prophecy, day of resurrection and justice.